2021
DOI: 10.1186/s12902-021-00906-3
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 and IL-10 gene polymorphisms and cirrhosis of liver risk from a comprehensive analysis

Abstract: Background Different inflammatory and immune cytokines play a key role in the development of cirrhosis of liver (CL). To investigate the association between interleukin-6,10 (IL-6,10) genes polymorphisms and CL risk through comparison of the allele and genotype distribution frequencies by meta-analysis. Methods A literature search covered with the PubMed, Embase, Cochrane Library, Web of Science, Google Scholar, SinoMed (CNKI and Wanfang) through 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The hub gene TNFRSF1A may offer value as a marker of PBC (58), and one GWAS study of 1,840 cases and 5,163 controls identified the TNFRSF1A rs1800693 SNP as a PBC-related risk factor (OR=1.23, 95%CI=1. 14 STRING network diagrams depicting interactions between human TNF-a or IFN-g and other genes. (A, B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hub gene TNFRSF1A may offer value as a marker of PBC (58), and one GWAS study of 1,840 cases and 5,163 controls identified the TNFRSF1A rs1800693 SNP as a PBC-related risk factor (OR=1.23, 95%CI=1. 14 STRING network diagrams depicting interactions between human TNF-a or IFN-g and other genes. (A, B).…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors and cytokines such as members of the interferon (IFN) and tumor necrosis factor (TNF) family are vital components of host immune activity that can shape viral infection-related processes and the subsequent development of fibrosis (12, 13). In a prior study, our group conducted a meta-analysis examining the relationship between mutations in the IL-6 and IL-10 genes (rs1800871, rs1800872, rs1800795, rs1800796, rs1800797, rs1800896) and LC risk, ultimately identifying the IL-10 -592 and -1082 polymorphisms as being closely linked to LC susceptibility (14). Other reports have specifically focused on links between IFN-g and TNF-a genes polymorphisms and cirrhotic disease (15).…”
Section: Introductionmentioning
confidence: 99%
“…IL-6, a primary immunomodulatory cytokine, has been shown related to liver cirrhosis in a few studies. Zheng et al (2021) identified three polymorphisms in IL-6 gene and perform a meta-analysis to explore their association with liver cirrhosis. Five polymorphisms (rs1474347, rs10499563, rs2069837, rs1800795, rs1800796) in IL-6 gene were also identified in our systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…So far, several common inflammatory factors gene polymorphisms in liver cirrhosis have been investigated by meta-analysis ( Chen et al, 2011 ; Guo et al, 2015 ; Guo et al, 2018 ; Zheng et al, 2021 ; Liu and Yang, 2022 ). However, to our knowledge, there has not been a systematic review and meta-analysis that has comprehensively assessed the association of inflammatory factors gene polymorphisms with liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…Minghui et al. defined that the rs1800896 polymorphism may be linked to the risk of susceptibility to liver cirrhosis (Zheng et al., 2021).…”
Section: Introductionmentioning
confidence: 99%